1980
DOI: 10.1088/0022-3727/13/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Driver gas flow with fluctuations

Abstract: A shock tube's driver gas can apparently provide flow with turbulent bursts. The fluctuations are interpreted using a boundary layer model of contact surface flow and results from a kinetic theory of turbulence. With this, a lower limit of 4 on the ratio of maximum to minimum turbulent intensities in contact surface instabilities has been estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We have previously confirmed that light attenuation is a direct measure oflocal N0 2 density by determining the extinction coefficient in a static environment with a range of pressures, which includes our operating conditions. 9 The value of the extinction coefficient obtained was quite consistent with the standard results. 4 We have confirmed that the observed fluorescence is a direct measure oflocal N0 2 density and a reliable indicator of N0 2 density fluctuations.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…We have previously confirmed that light attenuation is a direct measure oflocal N0 2 density by determining the extinction coefficient in a static environment with a range of pressures, which includes our operating conditions. 9 The value of the extinction coefficient obtained was quite consistent with the standard results. 4 We have confirmed that the observed fluorescence is a direct measure oflocal N0 2 density and a reliable indicator of N0 2 density fluctuations.…”
supporting
confidence: 87%
“…Indeed, the shock tube's contact surface has already provided some evidence of a coupling of turbulent effects with a nonequilibrium reaction. 9 Evidence of fully developed turbulence is found, in the sense that the fluctuation spectra show a power-law decay (i.e., Po:.wn) and the correlation profiles r ( 7) show appropriate time and length scales. Here we report on the most prominent features of the turbulent density fluctuations in a contact surface and the possibility of a direct relationship between the strength of turbulence and the rate of propagation of an exothermic molecular process.…”
Section: Introductionmentioning
confidence: 97%
“…18 A TSI three-dimensional laser doppler velocimeter (LDV) system is used to confirm the existence of turbulence in all three components of the local velocity at the contact surface; it consists of a 6-W Ar-ion laser, a color separator, a color link (photo multiplier tubes and amplifiers), a burst correlator (signal processor) and a 486 computer controller. For seeding the flow, 0.8-/xm latex particles and incense smoke were used on both driver and driven sections.…”
Section: Experimental Facilities and Test Conditionsmentioning
confidence: 99%
“…The observed grain size of the fibre in the perpendicular direction is ca. 5 nm (W hittaker et al 19906) and this is relatively insensitive to h eat tre a tm e n t (Johnson et al 1980). The actual value for Af± will depend on the value selected for a which, in view of the disordered arrangem ent of layer planes norm al to th e fibre axis, clearly should be greater th an 2.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%